Evaluasi Air Buangan Domestik Sebagai Dasar Perancangan Rehabilitasi Instalasi Pengolahan Air Limbah (IPAL) Domestik Komunal Kampung Kandang, Desa Condongcatur, Yogyakarta - Utami, Ayu; Nugroho, Nandra Eko; Febriyanti, Salam Via; Anom, Thamzez Nuur; Muhaimin, Ahmad (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2019)
As population increases, domestic wastewater generated will increase as well. Domestic wastewater needs to be treated properly so as not to pollute the recipient's water body. Kampung Kandang already has a communal domestic wastewater treatment plant (WWTP) to treat domestic wastewater generated by citizens. The problem from the citizens is that the WWTP needs to be rehabilitated because the amount of sludge floating in the first biological treatment tank and still has a disturbing odor. Alternative solution for this problem is by rehabilitating WWTPs so that their functions are more optimal. The purpose of this study was to evaluate domestic wastewater in Kampung Kandang. The methods used in evaluating the wastewater i.e. analysis of primary data, calculation of standard stream evaluation and calculation of removal percentage. Communal Domestic WWTP needs to remove COD, BOD, TSS, Ammonia, and Total Coliforms parameters of 97.7%, 98.9%, 42.7%, 95.6%, and 99.9%. WWTP has already removed the TSS and ammonia. BOD, COD, and total coliform should be reduced by WWTP as much for each parameter are 25, 9%, 35%, and 95, 83%. Wastewater evaluation data can be used as a basis for the design of rehabilitation to be carried out at the Communal Domestic WWTP in Kampung Kandang.